THE USE OF SIGN-SIGN TERMS IN VARIOUS FIELDS - Salayeva Nargiza (Лучшие интеллектуальные исследования, 2023)
Annotation: Sign-sign terms are linguistic constructs that involve the repetition of a word or term to emphasize its significance, often used in different fields of study. This article delves into the significance and usage of sign-sign terms across various disciplines. We employ a multidisciplinary approach, combining linguistic analysis with insights from applied sciences to shed light on this intriguing linguistic phenomenon.